2005
DOI: 10.1080/09537100500163424
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the purinergic receptor P2Y12potentiates platelet shape change by a Rho kinase-dependent mechanism

Abstract: ADP activates human platelets through two G-protein coupled receptors, P2Y1 and P2Y12, to induce a range of functional responses. Here we have addressed the role and mechanism of P2Y12 in modulating ADP-induced platelet shape change. Although the response depended upon activation of P2Y1, it was potentiated by P2Y12 as the P2Y12-selective antagonists AR-C69931MX and 2MeSAMP partially inhibited shape change in the later phase of the response. This was paralleled by inhibition of pseudopod formation, platelet sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…1C). Combined ADP receptor blockade with the P2Y 1 receptor antagonist A3P5P (200 μ m ) and the P2Y 12 receptor antagonist 2‐MeSAMP [35] (10 μ m ) did not inhibit shape change (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…1C). Combined ADP receptor blockade with the P2Y 1 receptor antagonist A3P5P (200 μ m ) and the P2Y 12 receptor antagonist 2‐MeSAMP [35] (10 μ m ) did not inhibit shape change (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Formerly, the P2Y12 and P2Y13 receptors were believed to activate Gi coupled signaling cascade that causes inhibition of stimulated adenylyl cyclase (Hollopeter et al, ; Zhang et al, ; Fumagalli et al, ). Two independent groups revealed the P2Y12‐mediated activation of RhoA and Rho‐associated coiled‐coil‐containing protein kinase (ROCK) that reorganized the actin cytoskeleton in a Gi‐independent manner in the platelet (Soulet et al, ; Hardy et al, ). In addition, Malaval et al () reported the activation of RhoA/ROCK1 under the P2Y13 signaling cascade in hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Indomethacin-treated (10 M) washed platelets (2 ϫ 10 8 /ml) were treated with the Rho kinase inhibitor, Y27632 (10 M) (Sigma), and/or the intracellular Ca 2ϩ chelator, BAPTA-AM (20 M) (Sigma), or vehicle control, for 10 min as before (38). Wnt3a (50 nM) or its carrier was added for 1 min before platelet stimulation with 5 M ADP or 1.5 M TRAP in a Chrono-log aggregometer under stirring in the presence of 1 mM EGTA.…”
Section: Methodsmentioning
confidence: 99%